ANALYSIS OF LEVERAGE ON FIRM VALUE THAT IS MODERATED BY CARBON EMISSION DISCLOSURE - Umi Hanifah; Rayhan Gunaningrat (Proceeding of International Conference on Science, Health, And Technology, 2022)
The purpose of this study is to investigate the role of carbon emission disclosures in moderating the effect of firm characteristics such as leverage on firm value. This study's sample companies are manufacturing firms that are listed on the Indonesia Stock Exchange between 2015 and 2021. Leverage are the independent variables in this study. The dependent variable in this study is the company's value, and the moderating variable is carbon emission disclosure. The fixed effect model is the analytical method used. According to the test results leverage has no direct positive effect on firm value and leverage has a negative effect on firm value that is moderated by CED.